Jesus and The Restoration of Israel : A Critical Assessment of N.T. Wright's Jesus and the Victory of God - Edited by Newman, Carey C (Downers Grove InterVarsity Press, 1999)
A collection of essays written by various theologians and scholars. Each essay critically analyzes historical and biblical records of the life of Jesus Christ.
Keywords: Historicity of Jesus Christ -- Jesus and the victory of God (Wright, N.T.) -- Jesus Christ